Desempenho aerodinâmico de uma turbina eólica em escala, perfil NREL S809, com diferentes velocidades específicas de projeto - Diniz, Marco Antonio Bezerra (2014)
The constancy of Brazilian winds and the need to mitigate the demand of large cities have found in wind energy a strong partner. As an alternative for the production of electrical power, modern buildings and condominiums, plus some rural applications, have resorted to small wind turbines as an alternative to solve your needs. However, most of the technology found in the market is imported and has not been developed exclusively for applications in Brazil. The most important tool in experimental aerodynamics is the wind tunnel. Scale controlled experiments provide a large number of reliable data, besides providing security to those who handle. Given its importance, this paper aims at the development, prototyping, and understands the behavior of a wind turbine rotor scale subjected to wind tunnel tests and compares the results with those in the literature for a prototype scale real. Therefore, it required the use of correction techniques blockage effects of the wind tunnel. It was designed and manufactured 4 sets of rotors with values specific tip speed of 6 to 9 (λp=6, 7, 8 e 9). The tests were conducted in a wind tunnel where velocity data free stream, stream velocity with the turbine in operation, and angular speed and torque generated by the blades, was collected in order to know the curve of each rotor. It was observed that in situations where the flow speeds are not representative enough to reach the higher values of λ range between 3 and 5,6, indicates a design with λp=6. Already in situations where the values of λ ranging between 4,7 and 7,3, λp=7 proved to be more efficient. Have λp=9 proved to be no advantage in comparison to other projects. By comparing the data obtained in this work with the literature and the BEM, it can be stated that the study of wind turbines in a wind tunnel is quite reliable.